Recent Advances in Cell Membrane Coated-Nanoparticles as Drug Delivery Systems for Tackling Urological Diseases - Cenchao Yao; Dahong Zhang; Heng Wang; Pu Zhang (MDPI AG, 2023)
Recent studies have revealed the functional roles of cell membrane coated-nanoparticles (CMNPs) in tackling urological diseases, including cancers, inflammation, and acute kidney injury. Cells are a fundamental part of pathology to regulate nearly all urological diseases, and, therefore, naturally derived cell membranes inherit the functional role to enhance the biopharmaceutical performance of their encapsulated nanoparticles on drug delivery. In this review, methods for CMNP synthesis and surface engineering are summarized. The application of different types of CMNPs for tackling urological diseases is updated, including cancer cell membrane, stem cell membrane, immune cell membrane, erythrocytes cell membranes, and extracellular vesicles, and their potential for clinical use is discussed.